In House Training terhadap Pengetahuan dan Implementasi Pelaksanaan Metode Tim (Journal of Telenursing (JOTING), 2025)
This study aims to identify the effect of in-house training on knowledge and implementation of team method implementation in the inpatient ward of Ciremai Hospital, Cirebon in 2023. The method used is quantitative with a quasi-experimental design and a pre-experimental approach and a one group pre and post design. The results of the study showed that there was a change in the average value of knowledge about nursing rounds before in-house training with an average value of 56.98 and after in-house training with an average value of 74.58. There was a change in the implementation of appropriate nursing rounds before in-house training as many as 66 respondents (67.7%) and after in-house training, appropriate implementation was carried out as many as 77 respondents (80.2%). In conclusion, there is an effect of in-house training on knowledge and implementation of team method implementation in the inpatient ward of Ciremai Hospital, Cirebon in 2023.Keywords: In-House Training, Knowledge, Team Method.